Dakwah Islam melalui Kesenian Musik Sufi pada Grup Band Debu - Fitriyani Fitriyani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Nowadays Islamic preaching is too monotonous and boring, so that the preaching material only reaches the mind and does not reach the human heart or spirituality. Therefore, a new method of preaching is needed, as has been done by the Debu Band Group. This research aims first, to explain Sufi arts performed by the band Dust. Second, explaining the message of da'wah contained in the song lyrics sung by the band Debu. Third, the innovation of da'wah carried out by the band Debu. This research uses a case study approach. The results of this research found that first, the dust band group, like early Sufi music, used musical instruments such as pipes, flutes and drums, they also used similar instruments such as Santur, Tambura, gendok-gendok, tambourine and others combined. with the harmony of modern musical instruments. secondly, apart from being a place for entertainment for the community, the dust band group is also a medium for da'wah, namely a medium for artistic da'wah in the field of music, where the elements of da'wah such as creed, worship and sharia are often found in the lyrics of the songs that are sung and become a da'wah message. for his listeners. Third, the da'wah innovation carried out by the band Debu is a change in the elements of da'wah such as materials, methods, preaching and preaching media.